Among singers, matrons and poets: meaning the blues (Orfeu, 2022)
This article addresses the blues. Its purpose is to analyze striking aspects of the aesthetics and language of this secular African American musical genre: the bittersweet discursive, emotional, and behavioral ambiguity, a culturally codified language whose common thread is linked to the concept(s) of meaning. Analytical axes were chosen centered on the reflexive tetrad of structure, process, function, and meaning. The path that enables the analysis of this artistic manifestation is a bibliographic review that makes use of the theoretical and methodological framework of Cultural Musicology, Ethnomusicology, and Musical Semiology. It also resorts to other theoretical supports from areas such as Anthropology, History, and Literary Studies. The close relationship of blues aesthetics, language, and discourse - semantics and syntax - with the socio-historical and cultural construction of African American ethnic identity is also addressed.
Keywords: blues; emotion; musical semantics; signifying; meaning